Synthesis, Thermal, DFT Calculations, HOMO-LUMO, MEP, and Molecular Docking Analysis of New Derivatives of Imidazolin-4-Ones - Khedidja Merdja; Choukry Kamel Bendeddouche; Mokhtaria Drissi; Farah Chafika Kaouche; Nassima Medjahed; José Manuel Padrón; Mansour Debdab; Mustapha Rahmouni; El Habib Belarbi (Indonesian Journal of Chemistry, 2023)
This work focuses on synthesizing new imidazolin-4-one derivatives (2a-c), akin to leucettamine B analogs, via microwave-assisted transamination reactions. This reaction was carried out between 3-alkyl-5-dimethylamino-2-thioxo-imidazolidin-4-one (1a-c) and aniline. The structural integrity of the synthesized compounds was confirmed using NMR and MS spectroscopy, and their configurations were validated through DFT calculations. Analyses encompassed molecular electrostatic potential, frontier molecular orbitals, HOMO-LUMO energies, energy band gap, and global chemical reactivity descriptors, providing comprehensive insights into their characteristics. The investigation extended to the biological domain, employing substance activity spectra prediction (PASS) and molecular docking with Autodock Vina4 program. Notably, this holistic assessment aimed to gauge the potential regulatory effect of the compounds on cholesterol. This integrated approach contributes to compound design understanding and potential applications, spanning drug design and broader biomedical contexts.